Sorafenib for advanced hepatocellular carcinoma (HCC): impact of rationing in the United Kingdom - Palmer, D H (Nature Publishing Group, 2013)
BACKGROUND: The prognosis for hepatocellular carcinoma (HCC) is dependent upon tumour stage, performance status (PS), severity of underlying liver disease, and the availability of appropriate therapies. The unavailability of sorafenib may have a significantly adverse effect on the prognosis of UK patients with advanced HCC. During the study period, access to sorafenib was at the discretion of local health funding bodies, a process that may delay or deny access to the drug and that remains in place for Wales, Scotland, and Northern Ireland. Here, we attempt to address the impact of this system on patients with advanced HCC in the United Kingdom. METHODS: This is a retrospective study performed in the two largest specialist hepatobiliary oncology units in the United Kingdom. Funding applications were made to local funding bodies for patients with advanced HCC for whom sorafenib was considered appropriate (advanced HCC not suitable for loco-regional therapies, compensated chronic liver disease, PS 0–2). RESULTS: A total of 133 applications were made, of which 57 (43%) were approved and 76 (57%) declined. Demographics and prognostic factors were balanced between the two groups. This cohort had a number of adverse prognostic features: patients were predominantly PS 1–2; the majority had multifocal disease with the largest lesion being >5 cm; and macroscopic vascular invasion, metastases, and AFP >1000 ng ml(−1), were each present in one-third of cases. The median time from application to funding decision was 17 days (range 3–260 days). For the primary ‘intention-to-treat' analysis, median overall survival was 4.1 months when funding was declined, and 9.5 months when funding was approved (hazard ratio (HR) 0.48; 95% CI 0.3186–0.7267; P=0.0005). CONCLUSION: These data support the use of sorafenib for patients with advanced HCC as an effective intervention. In the United Kingdom, this applies to a relatively small group of patients, estimated to total ∼800 per year who, unfortunately, do not survive long enough to themselves lobby for the availability of this drug. These data provide a comparison of sorafenib with supportive care and demonstrate the potential detrimental impact on patient outcomes of rationing health-care resources on the basis of cost.